The influence of organic matter on the metabolism of some isolated microphyte algae of the Black Sea phytoplankton - Mihnea, Pia Elena (Cercetări Marine - Recherches Marines, 2026)
The results obtained on three unicellular algae grown in a medium with organic addition are shown. The influence of organic substances is represented as division rate. In order to avoid the influences of other factors on algae metabolism (viz. microelements and vitamins) we tested the cultivation of algae both in media containing these factors, as well as in media lacking them. The results obtained undoubtedly show the Importance of organic substance on the metabolism of algae.